Optical Fiber Semi-Distributed Interferometer Assisted by an FBG for Thermorefractometry and Sweat Sensing - Kulyan Karipbayeva; Wilfried Blanc; Daniele Tosi (Institute of Electrical and Electronics Engineers (IEEE), 2023)
Among optical fiber biosensors (OFB), the use of thermorefractometry is a promising approach for dual detection of refractive index (RI) and temperature with a single device, and it can find application in sweat analytes. We propose an optical fiber-based thermorefractometer made of a semi-distributed interferometer (SDI) supported by fiber Bragg gratings (FBGs), for the possible application of the detection of sweat biomarkers. The sensor is composed of two parts (SDI and FBG) integrated into a compact probe; the resulting spectrum is a composition of a periodic-like pattern throughout the whole spectrum (SDI) and a narrow-band reflection peak at the Bragg wavelength (FBG). The thermorefractometer detects the RI changes with a sensitivity of 75.752 dB/RIU, while the FBG detects thermal changes at 9.94 pm/°C with negligible cross-sensitivity. We demonstrate the use of the SDI/FBG probe for the detection of two sweat markers. We tested the performance of the sensor in artificial sweat with azelaic acid and suberic acid achieving a sensitivity of 0.629/% dB and −0.088 dB/%.
Keywords: Interferometry; Optical fiber; Materials science; Fiber optic sensor; Fiber Bragg grating; Optics; Fiber; Optical sensing; Optoelectronics; Physics; Composite material; type of access: open access